PREVALENCE OF ECTO PARASITES AND COMPARATIVE EFFICACY OF DIFFERENT DRUGS AGAINST TICK INFESTATION IN CATTLE - M. Ramzan; M. S. Khan; M. Avais; J. A. Khan; K. Pervez; W. Shahzad (Journal of Animal and Plant Sciences, 2008)
The present study was designed to find out the prevalence of ecto-parasites and to evaluate and compare the efficacy of ivermectin, doramectin and Azadirachta indica (neem) leaves against tick infestation in cattle. For this purpose a total of 300 cattle were examined for the prevalence of ecto-parasites in and around Dera Ghazi Khan (Pakistan). The prevalence of ticks, mites and lice was found to be 108 (36%), 15 (5%) and 24 (8%), respectively. The main species of ecto-parasites observed were Boophilus microplus, Boophilus annulatus, Hyalomma aegyptium, Psorcoptes bovis, Sarcoptes Scabies var bovis, Haematopinus tuberculates and Linognathus vituli. The efficacy of ivermectin, doramectin and Azadirachta indica (neem) against ecto parasites was 100%, 60% and 0%, respectively. From this study it was concluded that ivermectin is drug of choice against ecto-parasites of cattle.
Keywords: Ivermectin; Doramectin; Azadirachta indica; Prevalence; Ecto-parasites